Perceived social support from parents, teachers, and friends as predictors of test anxiety in Chinese final-year high school students: the mediating role of academic buoyancy - Li, Danwei; Ahmad, Nor Aniza; Roslan, Samsilah (Multidisciplinary Digital Publishing Institute, 2025)
A pervasive and significant academic challenge confronted by students on a global scale is the phenomenon of test anxiety. This phenomenon is exacerbated in China, especially among final-year high school students who face college entrance exams. Perceived social support is widely regarded as the most prevalent protective factor against test anxiety. Academic buoyancy also demonstrates a significant correlation with test anxiety. However, there has been limited research on the potential relationship between perceived social support, academic buoyancy, and test anxiety. The purpose of this study is to examine the effects of specific sources and types of students perceived social support (e.g., emotional support from parents, teachers, and friends) on test anxiety and examine whether academic buoyancy serves as a mediating variable in the relationship between perceived social support and test anxiety. A total of 565 final-year high school students were selected as respondents from Heilongjiang Province in China. The result of SEM analysis indicated that the three sources of student-perceived emotional support could not predict test anxiety directly, but the students perceived three sources emotional support may have an indirect effect on test anxiety through the mediating role of academic buoyancy. In particular, perceived friend emotional support is the most beneficial among these sources of support for students. The anticipated outcomes of this study are expected to provide educators, counselors, and parents with key insights into the factors that alleviate test anxiety in high school students.